2013
DOI: 10.1007/s10464-013-9587-1
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment–Education? A Fotonovela? A New Strategy to Improve Depression Literacy and Help‐Seeking Behaviors in At‐Risk Immigrant Latinas

Abstract: Research shows high risk for depression among immigrant Latinas known to increase during the acculturation process. Several barriers such as stigma and low health literacy result in an under-utilization of needed treatment among these women. In response, this study replicated the effectiveness of a Spanish language fotonovela, a form of Entertainment-Education (E-E), designed to increase depression literacy, decrease stigma, and increase help-seeking knowledge and behavior in Latinos. Specifically, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 48 publications
2
113
0
2
Order By: Relevance
“…All 75 at-risk Latina immigrants, who participated in the experimental group (Hernandez and Organista 2013), were invited to participate in structured qualitative interviews to explore their response to the depression literacy tool 3 weeks after exposure. With regard to recruitment of women into the quantitative randomized control study, the first author, with the assistance of promotoras, recruited participants from health education and parenting classes offered by a multiservice community clinic in the East Bay of San Francisco, as well as from 3 local Head Start programs where promotoras frequently recruited women for clinic classes (Hernandez and Organista 2013).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 75 at-risk Latina immigrants, who participated in the experimental group (Hernandez and Organista 2013), were invited to participate in structured qualitative interviews to explore their response to the depression literacy tool 3 weeks after exposure. With regard to recruitment of women into the quantitative randomized control study, the first author, with the assistance of promotoras, recruited participants from health education and parenting classes offered by a multiservice community clinic in the East Bay of San Francisco, as well as from 3 local Head Start programs where promotoras frequently recruited women for clinic classes (Hernandez and Organista 2013).…”
Section: Methodsmentioning
confidence: 99%
“…For a full description of Secret Feelings, see Cabassa et al (2012). In its previous evaluations, Unger et al (2012) as well as Hernandez and Organista (2013) found Secret Feelings to be highly effective in improving depression knowledge while reducing stigma towards depression treatment in samples of immigrant Latinos.…”
Section: Health and Mental Health Literacymentioning
confidence: 99%
See 2 more Smart Citations
“…İngilizce alanyazında da fotonovela kullanımı yaygın olmakla birlikte photonovels ile eş anlamlı kullanılması da söz konusudur. (Cabrera, Morisky ve Chin, 2002), alzheimer (Valle vd., 2006) veya depresyon (Cabassa vd., 2011;Hernandez ve Organista, 2013) gibi hastalıkların önlenmesi ve tedavisi konulu fotoromanlar sıklıkla tercih edilirken; araştırma sonuçları katılımcıların hastalığa ilişkin bilgilerinin arttığını, fotoromanları başkalarıyla paylaştıklarını ve okumaktan keyif aldıklarını gösterir.…”
Section: Alan Araştırmasıunclassified